Effect of variable thermal conductivity on convective heat and mass transfer over a vertical plate in a rotating system with variable porosity regime (Journal of Naval Architecture and Marine Engineering, 2014)
Mathematical model has been presented to investigate the effect of variable thermal conductivity on Darcy mixed convective heat and mass transfer flow past a vertical plate in a rotating system by taking into account of variable porosity regime and chemical reaction parameter. The governing boundary layer equations for the flow, energy and species are transformed into system of ordinary differential equations using similarity transformations and then solved numerically by employing Fourth order Runge-Kutta method with shooting technique for various values of physical parameters. The effects of variable thermal conductivity, chemical reaction parameter and variable porosity regime on the fluid velocity, temperature and concentration, local skin friction and rate of heat and mass transfer distribution in the regime are presented graphically and analyzed in detail. We compare the results with previously published work and good agreement is obtained.DOI: http://dx.doi.org/10.3329/jname.v11i1.16488